Genomes OnLine Database (GOLD) v.8: overview and updates. Issue Volume 49:Issue D1(2021) (5th November 2020) - Mukherjee, Supratim; Stamatis, Dimitri; Bertsch, Jon; Ovchinnikova, Galina; Sundaramurthi, Jagadish Chandrabose; Lee, Janey; Kandimalla, Mahathi; Chen, I-Min A; Kyrpides, Nikos C; Reddy, T B K
Abstract: The Genomes OnLine Database (GOLD) (https://gold.jgi.doe.gov/ ) is a manually curated, daily updated collection of genome projects and their metadata accumulated from around the world. The current version of the database includes over 1.17 million entries organized broadly into Studies (45 770), Organisms (387 382) or Biosamples (101 207), Sequencing Projects (355 364) and Analysis Projects (283 481). These four levels contain over 600 metadata fields, which includes 76 controlled vocabulary (CV) tables containing 3873 terms. GOLD provides an interactive web user interface for browsing and searching by a wide range of project and metadata fields. Users can enter details about their own projects in GOLD, which acts as a gatekeeper to ensure that metadata is accurately documented before submitting sequence information to the Integrated Microbial Genomes (IMG) system for analysis. In order to maintain a reference dataset for use by members of the scientific community, GOLD also imports projects from public repositories such as GenBank and SRA. The current status of the database, along with recent updates and improvements are described in this manuscript.